Pengaruh Pelatihan, Pengawasan dan Beban Kerja terhadap Kinerja Mitra Statistik pada Badan Pusat Statistik Kabupaten Tabanan - Lestari, Ni Putu Devi; Wijaya, Putu Yudy; Purwaningrat, Putu Atim (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2024)
Employees are an important component in achieving company goals. To achieve this goal, companies need human resources who have the best quality and quantity of work. The factors are training, supervision and workload which are believed to influence performance. The aim of this research is to determine the effect of training, supervision and workload on the performance of the Statistics Partners of the Tabanan Regency Central Statistics Agency. There were 64 statistical partners at the Tabanan Central Statistics Agency in this research sample. Utilizing the method of data analysis involves the application of multiple linear regression analysis to draw meaningful insights from the data at hand. The research results show that the performance of the Statistics Partners is positively and significantly partially influenced by training, supervision, while the workload is negatively and significantly at the Tabanan Regency Central Statistics Agency. The performance of Statistics Partners is simultaneously significantly influenced by training, supervision and workload at the Tabanan Regency Central Statistics Agency.